2000
DOI: 10.1097/00124509-200006000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Treatments for ECS-Induced Memory Deficits: A Review of Research and a Discussion on Animal Models

Abstract: During the last decade the use of herbal medicinal substances in the attenuation of anterograde and retrograde amnesia induced by electroconvulsive shock (ECS) has been studied using animal research. We will discuss the background of herbal medicine in India, review the research findings on herbal medicines for ECS-induced amnestic deficits, and examine the applications and limitations of animal models in this context. We will focus on our own research and insights, with particular emphasis on practical issues. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…animals with greater muscle mass, but also to very young animals (30). In the present survey, the weights of the animals that suffered spinal fractures ranged between 190 and 420 g. This large range, in addition to missing data regarding exact body weight at the time of fractures for studies 1-21, makes it difficult to draw any final conclusions about the relationship between weight and fracture incidence.…”
Section: Skeletal Fractures After Electroconvulsive Seizures In Ratmentioning
confidence: 64%
See 1 more Smart Citation
“…animals with greater muscle mass, but also to very young animals (30). In the present survey, the weights of the animals that suffered spinal fractures ranged between 190 and 420 g. This large range, in addition to missing data regarding exact body weight at the time of fractures for studies 1-21, makes it difficult to draw any final conclusions about the relationship between weight and fracture incidence.…”
Section: Skeletal Fractures After Electroconvulsive Seizures In Ratmentioning
confidence: 64%
“…However, depending on the specific research aims, it is not always feasible to implement a modified ECS method, as the results may become inconsistent. It has been suggested that the use of anaesthetic agents affect the cognitive deficits after electroconvulsive treatment and that these agents might have anticonvulsant effects (21,30,38,39). The use of anaesthesia has also been reported to preserve some memory functions when administered before/during ECS (15,38,40).…”
Section: Risk Factors For Ecs-induced Fracturesmentioning
confidence: 99%
“…Laboratory studies by Aulakh et al (1988) and Purohit et al (1996) revealed the herb as anticatatonic and a central nervous system depressant with an LD50 of 450 mg/kg (Agarwal and Day, 1977). By contrast, Andrade et al (2000) found no significant benefit to promote learning or correct amnesia when Evolvulus alsinoides was tested. Still, dozens of studies have been made of the compound herbal preparation called BR-16A and marketed as Mentat (e.g., Tripathi et al, 2000).…”
Section: Chemistry and Laboratory Experimentsmentioning
confidence: 72%
“…This drug contains 20 or more plants species, including Evolvulus alsinoides, and has shown positive results like those reported by Aulakh et al (1988) and Purohit et al (1996). Reasons for the different interpretations remain unknown, but Andrade et al (2000) suggested that they may have been due to their using an aqueous as contrasted with alcoholic extracts by others. More may be involved as the Ayurvedic preparations are typically aqueous.…”
Section: Chemistry and Laboratory Experimentsmentioning
confidence: 99%
“…Erhöhte Cortisolspiegel scheinen ebenso die Vulnerabilität des Gehirns bezüglich kognitiver Beeinträchtigungen zu verstärken. Welche Bedeutung Kräuterextrakte dabei spielen ist weiterhin offen; tierexperimentelle und erste klinische Erfahrungen zeigen eine bestimmte, aber noch mit Vorsicht zu interpretierende nootropische Wirksamkeit [65,66]. Eine Untersuchung an 16 EKT-Patienten mit depressiver Grunderkrankung zeigte eindeutig einen Zusammenhang zwischen erhöhten Glucocorticoiden im Serum und Minderung exekutiver Funktionen, Verarbeitungsgeschwindigkeiten und verbalem Gedächtnis [67].…”
Section: Prävention Und Therapie Von Kognitiven Störungen (S Tab 3)unclassified